Middle Triassic (Anisian-Ladinian) Tejra red beds and Late Triassic (Carnian) carbonate sedimentary records of southern Tunisia, Saharan Platform: Biostratigraphy, sedimentology and implication on regional stratigraphic correlations. (January 2017) - Soussi, Mohamed; Niedźwiedzki, Grzegorz; Tałanda, Mateusz; Dróżdż, Dawid; Sulej, Tomasz; Boukhalfa, Kamel; Mermer, Janusz; Błażejowski, Błażej
Abstract: The "red beds" of the Triassic succession outcropping at Tejra-Medenine (southern Tunisia, Saharan Platform) have yielded rich fossil assemblages of both freshwater and brackish-marine invertebrates and vertebrates. The new discovered fauna indicates an Anisian-Lower Ladinian age for the Tejra section. Its lowermost part is considered as equivalent of Ouled Chebbi Formation, while the medium and upper parts are considered as equivalent of the Kirchaou Formation. Both sedimentological characteristics and fossil assemblages indicate the increasing marine influences within the middle part of the section and the migration of brackish and freshwater fauna into the lacustrine/playa environment at the top. The marine fauna-rich interval of the Tejra section correlates well with the well-known Myophoria -rich carbonate stratigraphic marker confirming the Middle Triassic (Ladinian) major transgression well recorded eastward in the Tunisian Jeffara basin and in Libya. The use of this Ladinian stratigraphic event in addition to the Carnian carbonate transgressive events of the Jeffara escarpment outcrops was of great help for regional lithostratigraphic correlations between the Triassic outcropping series and those currently buried in Ghadames and Berkine basins. The age of the sandstones of "Trias Argilo-Gréseux Inférieur" (TAGI) which forms the main oil and gas reservoir in the Saharan domain is attributed to the Anisian-Carnian and considered as coeval of Ouled Chebbi and Kirchaou Formations of the Dahar escarpment. An updated synthetic stratigraphic chart is proposed for the Triassic of Saharan Platform domain on the basis of the compilation of the new obtained results and the subsurface data taken from published literature. Highlights: The Middle Triassic succession of Tejra-Medenine site is characterized by a fauna grouped into two freshwater and one shallow-marine assemblages. Horseshoe crab recorded for the first time in the Middle Triassic of Africa. New accurate direct dating (Anisian-Ladinian) is provided for this succession and shallow-marine fauna from Tejra section was correlated with the first marine transgression of the Sahara Platform ( Myophoria rich-carbonate event). The Middle-Upper Triassic major floodings and associated carbonate sedimentary events, well defined in outcrops, are used in the present work as a time lines for regional correlations with the Triassic series intersected by petroleum wells drilled in the Ghadames-Berkine basins. The age of the main Triassic sandstones reservoir producing oil and gas in the Saharan Platform (TAGI) is discussed.